2016
DOI: 10.15621/ijphy/2016/v3i3/100850
|View full text |Cite
|
Sign up to set email alerts
|

Compare the Effectiveness of EMG Biofeedback Assissted Core Stability Exercises Versus Core Stability Exercises alone on Pain and Disability in Patients with Low Back Pain

Abstract: Background: Low Back Pain (LBP) is a health related problem than affects 80% of the population within the age limit of 15 to 45 years. The primary treatment used for patients with LBP includes muscle strengthening along with thermotherapeutic modalities. Thus the purpose of the study is to see the efficacy of EMG biofeedback assisted core stability exercises versus core stability exercises alone in patients suffering from pain and disability.Methodology: A total of 30 patients were divided through convenient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The conventional exercises also improved the peak value of muscle activation of the biceps femoris, but the average value of muscle activation showed insignificant improvement. Studies showed that exercises targeted to improve the core muscles' performance help develop more stability in the lower back and hence cause influences that reduce radicular pain [ 13 ]. The authors also stated that the Golgi tendon organs present in the tendons fire when a muscle is contracted or stretched [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The conventional exercises also improved the peak value of muscle activation of the biceps femoris, but the average value of muscle activation showed insignificant improvement. Studies showed that exercises targeted to improve the core muscles' performance help develop more stability in the lower back and hence cause influences that reduce radicular pain [ 13 ]. The authors also stated that the Golgi tendon organs present in the tendons fire when a muscle is contracted or stretched [ 14 ].…”
Section: Discussionmentioning
confidence: 99%